Asuhan Keperawatan Pada Pasien Dengan Chronic Kidney Disease (CKD) Stage V Diruangan Penyakit Dalam Rsup Dr. M. Djamil Padang - Syarifah Febiani; Kheniva Diah Anggita; Linda Marni; Aulia Asman (CV. ITTC INDONESIA, 2026)
Chronic Kidney Disease (CKD) is a progressive impairment of kidney function characterized by the inability of the body to maintain metabolic, fluid, and electrolyte balance, resulting in increased blood urea levels. The World Health Organization (WHO) reported 254,028 deaths caused by CKD in 2020 and more than 843.6 million global cases in 2021. According to the Indonesia Health Survey (SKI, 2023), the prevalence of CKD in Indonesia reached 0.18% or approximately 638,178 individuals. This study aimed to implement nursing care for CKD patients at RSUP Dr. M. Djamil Padang using a case study method conducted in the IW Wing B ward from February 2–6, 2025. The assessment of Mrs. M identified four nursing diagnoses, namely hypervolemia, ineffective breathing pattern, decreased cardiac output, and impaired urinary elimination. Interventions included hypervolemia management, airway management, cardiac care, and urinary elimination management. Evaluation results showed reduced hypervolemia and impaired urinary elimination, while breathing patterns and cardiac output improved. Systematic nursing care was shown to reduce symptoms, prevent complications, and improve patients’ quality of life.